The impact of creatine supplementation on the development of kidney disease – literature review - Mateusz Matczak; Karol Jasiński; Aleksandra Broda; Kacper Hoksa; Krzysztof Jodłowski; Ewa Dubniewicz; Paula Majewska; Alicja Staszek; Wiktoria Łoskot; Jan Szwech (Quality in Sport)
Introduction: Creatine, a widely studied dietary supplement, is known for enhancing athletic performance and muscle strength. Concerns persist regarding its impact on kidney health, as it raises serum creatinine levels, potentially confounding renal function assessments. This review examines creatine’s role in sports and clinical contexts, emphasizing safety and kidney health implications.